Smoking Is Associated with Pain in All Body Regions, with Greatest Influence on Spinal Pain. Issue 9 (3rd October 2019) - Smuck, Matthew; Schneider, Byron J; Ehsanian, Reza; Martin, Elizabeth; Kao, Ming-Chih J
Abstract: Objective: Examine the interrelationship between smoking and pain in the US population. Design: A cross-sectional population-based study. Setting: Nationwide survey. Methods: Comprehensive pain reports categorically defined as head, spine, trunk, and limb pain; smoking history; demographics; medical history from a total of 2, 307 subjects from the 2003–2004 National Health and Nutrition Examination Survey obtained from the Centers for Disease Control were analyzed. Unpaired t tests were used to analyze independent continuous variables, and chi-square tests were used to analyze categorical variables between smoker and nonsmoker groups. Weighted multivariate logistic regression analyses determined the association of current smoking with the presence of pain in various body regions. Results: Smoking is most strongly associated with spine pain (odds ratio [OR] = 2.89, 95% confidence interval [CI] = 2.21–3.77), followed by headache (OR = 2.47, 95% CI = 1.73–3.53), trunk pain (OR = 2.17, 95% CI = 1.45–2.74), and limb pain (OR = 1.99, 95% CI = 1.45–2.73). Conclusions: Current smoking is associated with pain in every region of the body. This association is strongest for spine and head pain. Given that pain is a strong motivator and that current smoking was associated with pain in all body regions, we recommend that these results be used to further raise public awareness about the potential harms of smoking.